Exploring Plagiarism into Perspectives of Indonesian Academics and Students - Rina Agustina; Pambudi Raharjo (Journal of Education and Learning (EduLearn), 2017)
Plagiarism has been done by students from around the globes. There has been a heated discussion of finding reasons why plagiarism occurred in academic world and Eastern students in particular. This research wants to explore how actually students perceive plagiarism in their academic writing as well as how lecturers coped with plagiarism in the students’ assignments. The research participants were taken from 2 different majors, 32 English Education students and 10 Psychology students as well as 5 lecturers from English Education Department and 3 lecturers from Psychology Faculty in one of private universities in Central Java Province, Indonesia. Questionnaires were distributed to those respondents and also interviews were conducted to several lecturers and students. The results of questionnaire and interview showed that both students and lecturers knew and understand the essence of plagiarism, however, students admitted that they still plagiarised in their assignment. Lecturers, on the other hand, revealed that they could figure out when students plagiarised others’ works. However, it was limited to crossing over assignments between students. In other words, detecting plagiarism was done manually and restricted to students’ written works only. In conclusion, despite comprehending the meaning of plagiarism, student still plagiarised since there was not any real action from lecturers to encounter it.